Mechanisms of the carcinogenicity of nanomaterials - G. A. Belitsky; K. I. Kirsanov; E. A. Lesovaya; M. G. Yakubovskaya (Успехи молекулярной онкологии, 2022)
Nanomaterials become more widespread in the different areas of human life, forming the new technosphere philosophy, in particular, new approaches for development and usage of these materials in everyday life, manufacture, medicine etc.The physicochemical characteristics of nanomaterials differ significantly from the corresponding indicators of aggregate materials and at least some of them are highly reactive and / or highly catalytic. This suggests their aggressiveness towards biological systems, including involvement in carcinogenesis. The review considers the areas of use of modern nanomaterials, with special attention paid to the description of medicine production using nanotechnologies, an analysis of the mechanisms of action of a number of nanomaterials already recognized as carcinogenic, and also presents the available experimental and mechanistic data obtained from the study of the carcinogenic / procarcinogenic effects of various groups of nanomaterials currently not classified as carcinogenic to humans.Preparing the review, information bases of biomedical literature were analysed: Scopus (307), PubMed (461), Web of Science (268), eLibrary.ru (190) were used. To obtain full-text documents, the electronic resources of PubMed Central (PMC), Science Direct, Research Gate, Sci-Hub and eLibrary.ru databases were used.